Osteoporosis: prevention and personalized physiotherapy - Tiziana Nava (Verduci Editore, 2020)
Osteoporosis is a systemic disease of the skeleton characterized by reduction and alteration of the qualitative bone mass, accompanied by an increased risk of fracture. Regardless of whether it is primitive regarding postmenopausal women and older people or secondary determined by many diseases and the assumption of some drugs, osteoporosis is a condition for which preventive measures are very important, as well as treatments according to a patient's personal characteristics and age. Prevention must start early and be subsequently adapted to the various life cycles. The aim of this paper is to propose exercises with an evidence-based physiotherapy approach to the different age populations.